Study guides

Q: -3x-y equals 3 and -3x-5y equals -21 please help me solve the above equation through the substitution method.?

Write your answer...

Submit

Related questions

x+y=5

by elimination,substitution or through the matrix method.

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

-2

That's exactly the purpose of the substitution method ... to get an equation with one less variable. When you have it, you solve it for the variable that's left.

2x-3y=13

There are no disadvantages. There are three main ways to solve linear equations which are: substitution, graphing, and elimination. The method that is most appropriate can be found by looking at the equation.

Substitution method: from first equation y = 5x - 8. In the second equation this gives 25x - 5(5x - 8) = 32 ie 25x - 25x + 40 = 32 ie 40 = 32 which is not possible, so the system has no solution. Multiplication method: first equation times 5 gives 25x - 5y = 40, but second equation gives 32 as the value of the identical expression. No solution.

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

(2,3)

The substitution method undoes the chain rule.

From first equation, -y = 3x + 3. Substitute in second equation: -3x + 5(3x + 3) = -21 ie 12x = -36 so x = -3 and y = -(-9 + 3) = 6. Easier method: subtract first equation from second giving -4y = -24 so y = 6, this in first equation gives -6 = 3x + 3, ie 3x = -9 so x = -3

y = x - 7 x + y = 5 Substituting for y in the second equation, x + (x - 7) = 5 or 2x = 12 so that x = 6 Then, from the first equation, y = 6 - 7 = -1 So, (x, y) = (6, -1)

Ostrowski

From first equation: y = 2x - 5Substitute this in second equation: 3(2x - 5) - x = 5, ie 6x - 15 - x = 5ie 5x = 5 + 15 so x = 4 and y = 3

If the process of substituting leads to an identity rather than an equation then the system has infinitely many solutions.

Yes

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

z=pq

y = 17 + 2x from second equation, substitute in first equation: 2x + 6(17 + 2x) = -10 ie 2x + 102 + 12x = -10 ie 14x = -112 so x= -8 and -16 + 6y = -10 ie 6y = -10 +16 so y = 1 Other method: Add the two equations, giving 7y = 7 so y =1 and x = -8

-2

x=1, y=1

Solution can be found by using three methods: 1. Cross Multiplication Method 2. Substitution Method 3. Elimination Method Other Method can also be there but I don't know You can further get info about these method by searching these on Google Search.

Substitution method: y = 1 + x so 2x + (1 + x) = 4, ie 3x = 3 so x = 1 and y = 2

G-Given U-Unknown E-Equation S-Substitution S-Solve